2017
DOI: 10.5588/ijtld.16.0584
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the tuberculosis–depression syndemic to end the tuberculosis epidemic

Abstract: Tuberculosis (TB) and depression act synergistically via social, behavioral, and biological mechanisms to magnify the burden of disease. Clinical depression is a common, under-recognized, yet treatable condition that, if comorbid with TB, is associated with increased morbidity, mortality, community TB transmission, and drug resistance. Depression may increase risk of TB reactivation, contribute to disease progression, and/or inhibit the physiological response to anti-tuberculosis treatment because of poverty, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
133
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(139 citation statements)
references
References 78 publications
(138 reference statements)
5
133
0
1
Order By: Relevance
“…Therefore, non-language barriers to presentation such as stigma, TB knowledge and healthcare eligibility issues [7] may confound this relationship. Mental health barriers were associated with a doubling of presentation delay on complete case analysis, which would be consistent with the literature suggesting that mental health disorders (specifically depression) can delay healthcare seeking [14]. However, mental health barriers were not associated with presentation delay on sensitivity analysis removing the 1% of outlying (longest) delays, suggesting that our estimates for mental health barriers were overly influenced by cases with outlying delays.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, non-language barriers to presentation such as stigma, TB knowledge and healthcare eligibility issues [7] may confound this relationship. Mental health barriers were associated with a doubling of presentation delay on complete case analysis, which would be consistent with the literature suggesting that mental health disorders (specifically depression) can delay healthcare seeking [14]. However, mental health barriers were not associated with presentation delay on sensitivity analysis removing the 1% of outlying (longest) delays, suggesting that our estimates for mental health barriers were overly influenced by cases with outlying delays.…”
Section: Discussionsupporting
confidence: 86%
“…Poverty is a common driver of TB (WHO, 2013;Figueroa-Munoz and Ramon-Pardo, 2008;Lund et al, 2011) and mental illnesses (Lund et al, 2011). Mental illness can result from having TB disease because of stigma, social vulnerabilities such as malnutrition, and the side effects of TB drugs (Sweetland et al, 2017). The poor lack adequate housing and food; experience more stress than people who are better off; and lack access to health care.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, in spite of the implementation of these strategies, the access and detection of TB cases remain unchanged, mainly among those living in large urban areas, with drug resistance, vulnerable populations (HIV-infected individuals, inmates, drug users, homeless, children, and adolescents) or with comorbidities [human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS), mental health disorders, diabetes mellitus, and smoking] [6][7][8][9] .…”
mentioning
confidence: 99%
“…Recently, clinical and operational research have indicated that the approaches are more effective when they respond to local socio-cultural characteristics, organization of health service delivery, and type of community activities. These approaches should cover the cascade of actions that include local TB transmission control, screening, and diagnostic investigation of active and latent TB, followed by its antimicrobial treatment, incorporating biomedical approaches [9][10][11][12][13] , biopsychosocial 8,14 , strengthening social protection 15,16 , community participation 17 , and political commitment 18 . However, in high TB burden countries, operational research performed to cover such approaches are limited.…”
mentioning
confidence: 99%